Pemberian Creep Feed dengan Sumber Protein Berbeda terhadap Performa, Karkas, dan Kualitas Daging Domba Dorper: Effect of Creep Feed with Different Protein Sources on the Performance, Carcass, and Meat Quality of Dorper Sheep (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
The objective of this study is to evaluate the effectiveness of creep feed containing Indigofera and Black Soldier Fly (BSF) maggot meal and Indigofera on the performance and meat quality of Dorper lambs. The study involved 21 male lambs aged 3 months with an average weight of 20.03 ± 1.71 kg. A Completely Randomized Design (CRD) with 3 treatments and 7 replications was used, namely PM = Martabe feed, P1 = Indigofera creep feed, and P2 = BSF maggot creep feed. Parameters observed included performance, carcass characteristics, physical meat quality, nutrient composition, and fatty acid profile of Dorper lamb meat. Data were analyzed using Analysis of Variance (ANOVA), and significant differences were further analyzed using Duncan's test. The results showed that P2 significantly increased (p